Reconstruction Of Legislative Performance Measurement Model: Penta Helix Performance Measurement Model For South Tangerang DPRD - Mustopa Mustopa; Sadu Wasistiono; Muhadam Labolo; Tjahjo Suprajogo (Green Publisher Indonesia, 2024)
This study examines the urgency of reconstructing the performance measurement model of the Regional People's Representative Council (DPRD) in the context of government administration in South Tangerang City. Through a qualitative descriptive approach with a case study design, this study analyzes multidimensional problems that reflect systemic dysfunction in local governance. Based on the theory of power distribution and the concept of Penta Helix, this study develops the Penta-Helix Performance Measurement Model as a holistic and contextual performance evaluation instrument for the DPRD. The model integrates five key dimensions: Responsive Legislation, Effective Oversight, Substantive Representation, Policy Innovation, and Public Accountability. The findings of the study reveal a significant gap between the constitutional mandate of the DPRD and its implementation in the field, which is manifested in the phenomenon of increasing poverty rates, and performance suboptimality in the functions of legislation, supervision, and representation. This study concludes that the reconstruction of the DPRD performance measurement model is a strategic step in efforts to revitalize local democracy and optimize local governance in the era of autonomy.